Study of Road Damage Handling on Access Road to Soekarna – Hatta Airport North Perimeter – South Perimeter, Tangerang Banten - Sianturi, Ogung; Buana , Cahya (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Pavement damage on the North Perimeter – South Perimeter Road is quite extreme. The damage is 1 kilometer long for a total of approximately 6 kilometers. The damage occurred, such as potholes, bumpy roads, chipped asphalt, and large deflection occurred when heavy load vehicles pass on the road. The damage occurred due to loads of heavy vehicles transporting materials during the Road and Connecting Bridge Construction at Soekarno-Hatta Airport. In addition to being overloaded, the condition of drainage channels on the road could not function optimally. Based on the phenomenon, the pavement damage on the North Perimeter – South Perimeter Road needs to be repaired. Two types of primary data consisted of traffic and road damage data, and secondary data was Basic Unit Price Activity (BUPA) were used in construction planning. The data were processed and analyzed in several steps. First, it carried out the road damage surveyed visually and riding quality. Then, it conducted a characteristic survey of the traffic at this moment, and it was analyzed during the life of the plan. After that, the thickness planning of a road pavement structure was carried out and continued with cost analysis. Finally, it selected the most appropriate type of road pavement in terms of cost over the life of the plan. The results of existing data analysis obtained the rigid pavement type as a repair of damage to the North Perimeter Road - South Perimeter with a drainage layer thickness of 15 cm, 10 cm LMC foundation layer, and 28.5 cm thick concrete slab. The initial cost of construction and maintenance of IDR 34,231,907,890.